Optimalisasi Penggunaan Marketplace dan Digital Payment sebagai Solusi Pembelian pada UMKM Truveil.id - Maylani, Cindy; Khasanah, Retno Nur; Zuhri, Muhammad Fadli; Kustiningsih, Nanik (Universitas Nahdlatul Ulama Surabaya, 2022)
Technological developments in the current era are increasingly significant, especially in the trade sector. In addition, the presence of covid-19 and work from home makes online shopping one of the ways to carry out purchasing activities. In Indonesia, many people already understand technology or commonly called technology literacy, nowadays many people from various circles use e-commerce as a means of buying and selling for their daily needs. In addition, the rise of the marketplace is also one of the many drivers of change in trade transactions or buying and selling. This study aims to provide education whether the use of digital payments and marketplaces can be accepted by customers and is profitable for the seller, especially for UMKM Truveil.id. The research that we carried out used descriptive qualitative research methods in which we carried out the process through interviews, document studies and observations. The research was conducted by involving 10 of our consumers who carry out trade transactions on UMKM Truveil.id and there are about 3 people from the UMKM Truveil.id team. The results of the research conducted indicate that optimizing the use of digital payments and marketplaces can reduce payment difficulties and a sense of security for customers as well as ease of writing transaction books for sellers.